Digitilization of academic libraries, a response to the blended mode of teaching in private higher learning institutions in Africa - Nzeyimana, Damien; Mutethia, Paul; Gibendi, Ruth (African Journal of Science, Technology and Social Sciences, 2022)
ABSTRACT Academic libraries are being encouraged to digitalize their services. This idea has been supported with the advent of COVID-19 where health measures are encouraging social distancing and avoiding hand to hand distribution of documents and the limit of face to face contacts. Encouragement is being made to have a full online lectures or blended mode of teaching where there is a mixture of face to face with online courses. The main challenge in this process is that most of core books related to academic courses in libraries are in printed format and accessible only by visiting the library. It is to note that private higher learning institutions in Africa are still facing challenges related to inadequate resources as they do not get governmental finance support. This study aims to review literature on the role of digitalization of academic libraries as a response to the blended mode of teaching. The objective of the study is to investigate challenges faced by academic libraries in private higher learning institutions in Africa that limit them to satisfy their users’ needs through digitization of the library and to propose strategies that can be adopted in order to overcome those challenges. Literature reviewed found out that: The digitalization of library has a great role to play on library users’ needs satisfaction; That academic libraries are facing challenges during the digitalization process, challenges that limit fully adoption the use of internet and the digitalization of libraries in order to satisfy library users’ needs.The study recommends: the management to avail adequate resources to libraries; hiring new personnel and deploying/retraining existing staff in ICT related to library digitalization; Training of library users on the access and use of digitalized library resources; To embrace new technology and move from printed documents accessed physically to digitalized documents accessed through internet in order to meet the users’ needs satisfaction in the age of digitalization of education.